Retroperitoneal fetus in fetu in a 65-year-old man - Piltcher-da-Silva, Rodrigo; Sasaki, Vivian Laís; Piltcher-Recuero, Mariana; Chiconelli Zangari, Matheus Antonio; Bora Ruggeri, João Rafael; Cravo Bettini, Luiz Francisco; Trippia, Carlos Henrique; Alessi, Alexandre; Coelho, Júlio Cezar Uili; Anselmi Junior, Raul Alberto (Clinical and Biomedical Research, 2022)
Fetus in fetu (FIF) is a rare congenital anomaly in which a malformed fetus is incorporated within the body of its twin. It was first described in the late 18th century and has an incidence of 1:500,000 live births. In most cases, the diagnosis is made in infants or young adults. To date, the oldest patient reported in the literature was 47 years old. We describe the case of a 65-year-old patient with FIF, now the oldest reported in the literature. Our patient meets all the diagnostic criteria for FIF, including the presence of a limb in advanced formation inside the lesion. The treatment was surgical excision. FIF should be considered in the differential diagnosis of abdominal masses, typically recognized in infancy. Symptoms arise from mass effects. Surgical resection should be performed due to the potential for malignant transformation.